Pendidikan Kesehatan Home Care Pada Keluarga Dengan Anak Berkebutuhan Khusus - Kasmiati, Kasmiati; Jamin, Nunung Suryana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Children with special needs (ABK) are a group of children who require more attention in terms of their growth and development, health, and education. Their limitations often impact the need for specialized care at home. However, many families still lack the knowledge and skills to provide health care at home. This community service program aims to improve families' knowledge and skills in providing basic health care for children with special needs through home care education. Methods used include counseling, demonstrations of care practices, and group discussions. The results of the activity indicate an increase in families' understanding of home care, such as nutritional monitoring, personal hygiene, growth and development stimulation, and the management of simple health conditions. This program is expected to strengthen the role of families in supporting the quality of life of children with special needs.